Peranan Budaya Organisasi, Kemampuan Intelektual Terhadap Kinerja Dosen dan pengaruhnya terhadap Peningkatan Kesejahteraan Dosen - Agus Susanto (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2015)
The purpose of this study was to obtain empirical evidence and to determine the open-phenomena and conclusions regarding the effect of the role of organizational culture, intellectual ability, work environment, the performance STIE faculty performance, and its implications for improving the welfare of teachers. The method of research used descriptive and verification methods. The independent variable of the study are: the influence of the role of organizational culture (X1), intellectual ability (X2), and the work environment (X3), faculty performance (Y) as the intermediate variables and the dependent variable is the performance STIE (Z1) and welfare lecturer (Z2). The results of this study show that: (1) The Role of Organizational Culture, Intellectual Ability and Environment has a significant effect on performance of STIE Lecturer in North Sumatra, (2) Lecturers Performance have a significant influence on the performance of STIE, (3) The Performance of STIE have an influence significantly to improving the welfare of teachers.